Sintesis Dan Studi Molecular Docking Senyawa Pirazolo-Piridin Turunan Analog Kurkumin Monoketon Sebagai Inhibitor Enzim COX-2 - Enda Mora; Adel Zamri; Hilwan Y. Teruna; Neni Frimayanti; Ihsan Ikhtiarudin; Putri Rizki Rahmadani; Vella kurnia Wahyuni (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
The new pyrazolo-pyridine compounds derived from monoketone curcumin analogues (P4Cl and P2CL) were synthesized in two stages. The first stage was the synthesis of curcumin monoketone (Cs) analogue through the Claisen-Schmidt reaction in the heating method using reflux. The second step was the synthesis of P2CL and P4Cl through nucleophilic addition and intramolecular cyclization in the heating method using a Monowave 50 apparatus. The structures of the compounds P2CL and P4Cl were confirmed by spectroscopic analysis including UV-Vis, FT-IR, 1H-NMR and HRMS. Based on molecular docking studies, the compounds P2Cl and P4Cl have weak potential as COX-2 enzyme inhibitors with a binding free energy value of -4.02 kcal/mol and an RMSD of 1.19.